Faktor-Faktor yang Mempengaruhi Kinerja Dosen di Universitas Teknologi Surabaya - Suryowibowo, Dody Yanuar; Widodo, Agus Purbo (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
The goal to be achieved by the researcher in this case is to analyze the simultaneous or partial effect of leader behavior, motivation, preventive discipline, and ability on lecturer performance at the Surabaya University of Technology, and to determine the variables that have a dominant influence on the performance of lecturers at the Surabaya technology university. with the research instrument test method and Multiple Linear Regression Analysis. The respondents involved in this study were 31 people, who are permanent lecturers at the Surabaya Technological University. The results of this study indicate that there is a significant influence on the variables of leader behavior, motivation, preventive discipline, and the ability of lecturers simultaneously (simultaneously) on the performance of lecturers at the Surabaya Technology University. Furthermore, from this test, the variable of Lecturer Ability is the variable that has the most dominant influence on the performance of lecturers at the Surabaya University of Technology.